Standardized methods for photography in procedural dermatology using simple equipment. (15th February 2017) - Hexsel, Doris; Hexsel, Camile L.; Dal'Forno, Taciana; Schilling de Souza, Juliana; Silva, Aline F.; Siega, Carolina
Abstract: Photography is an important tool in dermatology. Reproducing the settings of before photos after interventions allows more accurate evaluation of treatment outcomes. In this article, we describe standardized methods and tips to obtain photographs, both for clinical practice and research procedural dermatology, using common equipment. Standards for the studio, cameras, photographer, patients, and framing are presented in this article.